Experimental investigation on fatigue behavior of butt-welded high-strength steel plates. (August 2021) - Tong, Lewei; Niu, Lichao; Ren, Zhenzhen; Zhao, Xiao-Ling
Abstract: This paper presents an experimental investigation into mechanical properties and fatigue performance of butt-welded high strength steel plates. Four typical high-strength steels (HSSs) were selected, with steel grades of 460, 550, 690, and 960 MPa. Mechanical properties were measured through monotonic tensile tests, cold bending tests, Charpy V-notch impact tests and hardness tests. A total of 114 fatigue tests were conducted on butt-welded high-strength steel plates. Comparisons of mechanical properties and fatigue performance are made among HSSs tested and conventional strength steels (CSSs) with a yield strength around 235 to 355 MPa. The natural slope of S–N curves for HSS butt-welded connections varied from 3 to 5. Two fatigue design approaches are recommended with one based on natural slope and one based on a fixed slope of 3 as for CSSs. Highlights: Four types of high-strength steel (HSS) were studied with yield stress up to 960 MPa. Measured mechanical properties of butt-welded high-strength steel plates. Conducted 114 fatigue tests on butt-welded high strength steel plates. Two approaches were recommended for fatigue design of butt-welded HSS connections.